410 km discontinuity sharpness and the form of the olivine alpha-beta phase diagram: Resolution of apparent seismic contradictions - Helffrich, G; Wood, B (1996)
Estimates of the thickness of the 410 km seismic discontinuity, believed to be due to the α-olivine→-β-modined-spinel transformation in olivine, are as low as 4 km based on discontinuity reflectivity. The seismically estimated thickness is, however, biased to values narrow than the true transformation interval if linear interpolation of properties is used lor modelling. A 5 km linear velocity gradient yields an average reflection coefficient identical to that of a 10 km transition interval based on olivine phase-diagram features. Moreover, alternative forms of the phase diagram, equally consistent with experimentally determined iron magnesium partitioning, on yield true transition intervals narrow as 4 km. This reconciles a discrepancy between phase equilibrium and seismic measures of discontinuity thickness in two ways: (1) seismic thickness estimates are too narrow; and (2) narrow transition intervals are permissible given existing phase-equilibrium constraints. Incorporating recent results on the influence of H2O on discontinuity properties, it appears that 410 km discontinuity reflectivity is much more sensitive to varying H2O concentration than to temperature, suggesting that discontinuity reflectivity variations reflect changes in mantle chemistry.